O SEBRAE e a consultoria para pequena empresa no Brasil: processos históricos e arranjos organizacionais nas últimas décadas. - Ralio, Vanise Rafaela Zivieri (Universidade Federal de São Carlos, 2015)
This project investigates the foundation and strengthening of SEBRAE institution, known as a reference in the consulting segment for micro and small enterprises in our country. For this purpose, makes an initial survey of scientific literature on the subject, beyond identifying and presenting some data and indicators related to small Brazilian companies, in order to demonstrate their actual importance in the Brazilian economic scenario. Then, it reexamines the consulting industry history in Brazil and in the world, resuming Consulting Cartography in Brazil and the studies conducted here about the sector. Finally, it presents the data identified about SEBRAE's trajectory since its birth and its development over the 40 years of its history. The study is based on the analysis of documents and data generated by the institution, publications about it, interviews with directors, employees and consultants, and it makes a general analysis of the institution from its activities in consulting, in order to identify and describe how it is made setting the agenda and products offered, the attended audience, the consulting agents, its organizational structure and the applied strategies for achieving their goals. As a result, it was possible to identify the major growth with consulting services as from changes in the strategies and products offered to different customers in all three stages presented: decades of 1970/1980, the 1990s and from 2000s, when it strengthens its performance in public policy, and its products are defined to micro and small enterprises, in addition to individual micro entrepreneurs, both formal and potential.
Keywords: Consulting; Small firms; SEBRAE; Empresas de consultoria; Pequena empresa; Serviço Brasileiro de Apoio às Micro e Pequenas Empresas; OUTROS